2021
DOI: 10.1111/1755-0998.13365
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐level genome of Poropuntius huangchuchieni provides a diploid progenitor‐like reference genome for the allotetraploid Cyprinus carpio

Abstract: Poropuntius huangchuchieni is a medium-sized freshwater fish species, belonging to the Poropuntius genus, which has a broad geographic distribution spanning from southwestern China to Myanmar, Thailand, the Malay Peninsula, and Sumatra (Kottelat, 2013) with the Mekong River System being the most likely center of diversity for the genus.In China, the genus is naturally distributed in the Yunnan Plateau, the southeastern neighbor of the Qinghai-Tibetan Plateau, which consistently responded to the Qinghai-Tibetan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The assembled genome spanned 1,103 Mb, with a contig N50 length of 1.52 Mb ( supplementary table S4, Supplementary Material online). Genome annotation showed that the Amur Ide genome comprises approximately 49.92% repetitive sequences ( supplementary tables S5 and table S6, Supplementary Material online), which was comparable to the repeat content of other Cypriniform species genomes ( Wang et al 2015 ; Xu et al 2019 ; Chen et al 2021 ). In the Amur Ide assembly, we predicted 27,633 protein-coding genes, of which 96.3% of the protein sequences showed similarity to protein sequences in public databases ( supplementary tables S7 and S8 and figs.…”
Section: Resultsmentioning
confidence: 69%
“…The assembled genome spanned 1,103 Mb, with a contig N50 length of 1.52 Mb ( supplementary table S4, Supplementary Material online). Genome annotation showed that the Amur Ide genome comprises approximately 49.92% repetitive sequences ( supplementary tables S5 and table S6, Supplementary Material online), which was comparable to the repeat content of other Cypriniform species genomes ( Wang et al 2015 ; Xu et al 2019 ; Chen et al 2021 ). In the Amur Ide assembly, we predicted 27,633 protein-coding genes, of which 96.3% of the protein sequences showed similarity to protein sequences in public databases ( supplementary tables S7 and S8 and figs.…”
Section: Resultsmentioning
confidence: 69%
“…For example, Onychostoma macrolepis has an estimated heterozygosity of 0.29% (L. Sun et al, 2020), Myxocyprinus asiaticus (Chinese high-fin banded shark) of 0.20% (Krabbenhoft et al, 2021), Gymnocypris przewalskii (Przewalskii’s naked carp) of 0.96% (Tian et al, 2022), and Poropuntius huangchuchieni of 0.68% (L. Chen et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“… 69 , 76 , 95 The genome sizes and gene numbers of these tetraploid fish were doubled compared with potential diploid ancestors P. huangchuchieni (1.02 Gb with 24,099 genes) and O. macrolepis (928 Mb with 24,770 genes), presumably due to WGD ( Supplementary Table S18 ). 77 , 96 The chromosome numbers in schizothoracine fish ranged from 92 to 96, which might result from the fusion of some chromosomes in the potential autotetraploidization. 69 …”
Section: Discussionmentioning
confidence: 99%